Assessing the proposed association between tooth agenesis and taurodontism in 975 paediatric subjects - ERIKA CALVANO KÃƒÆ’Ã…â€œCHLER, PATRÃƒÆ’Ã‚ÂCIA DE ANDRADE RISSO, MARCELO DE CASTRO COSTA, ADRIANA M (IAPD and Blackwell, 2008)
Tooth agenesis is the most common congenital anomaly in humans, and most cases are likely to be the result of many genes acting alone or in combination.